Understanding Graduating Pediatric Emergency Medicine Fellow Priorities for Career Pathways and Faculty Recruitment for Academic or Community Emergency Departments. Issue 1 (6th April 2020) - Sampayo, Esther M.; Agrawal, Pooja; Mittiga, Matthew R.; Klasner, Ann E.; Kim, In; Scarfone, Richard; Chang, Todd P.
Abstract: Objectives: Factors influencing the employment of pediatric emergency medicine (PEM) fellows in a career in academic medicine versus community emergency department (ED) settings have not previously been explored. The purpose of this study was to explore PEM fellows' priorities in selecting jobs and to identify factors that influence their decisions regarding career choices through a multicenter, qualitative approach. We also explored program directors' beliefs about graduates' job selection priorities. Methods: This was a cross‐sectional study among a convenience sample of PEM fellows and PEM fellowship program directors and/or associate program directors in the United States. The data were collected in 2017, using a qualitative methodology known as free listing. The fellows and program directors were solicited through the American Academy of Pediatrics Section on Emergency Medicine. Using content analysis, all free‐listing responses from participant samples were categorized into 14 distinct groupings. Thematic saturation was achieved, and member checking was performed to ensure trustworthiness. Results: A sample of 63 fellows from six geographically diverse programs and 41 program and/or associate program directors were surveyed. Location, schedule/work‐life balance and compensation were the most frequently cited factors taken into consideration for employment; these are not specific to PEM as a career choice. Other factors included patient population and ED resources. When deciding between academic and community employment, similar areas for the PEM physician emerged on both sides of the dichotomy: work–life balance, clinical hours, burnout, and acuity/patient complexity. Conclusions: There are universal factors that PEM physicians consider when choosing employment. The information elicited from this exploratory technique can inform content for national survey or other qualitative work to achieve richer descriptions of reported items and dichotomies to guide fellow recruitment and retention strategies.